2018
DOI: 10.18805/ijare.a-4807
|View full text |Cite
|
Sign up to set email alerts
|

Combining ability analysis for seed protein and methionine content in green gram [Vigna radiata (L.) wilczek]

Abstract: For combining ability analysis, a diallel method was employed in which eight genotypically diverse lines of green gram were crossed among themselves in all possible combinations excluding reciprocals. The analysis for combining ability revealed significant mean sum of squares of both general combining ability (GCA) and specific combining ability (SCA) for most of the characters which indicated the presence of both additive and non-additive gene actions. Higher magnitude of GCA effects than SCA effects were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 2 publications
2
5
0
Order By: Relevance
“…Thus, the significant assessments of both GCA and SCA variances indicated that both the additives and nonadditive nature of gene actions were engaged in controlling these characters in studied mungbean genotypes. These outcomes affirmed those discoveries by Reddy et al [33] Nath et al [44], Viraj et al [34], and Sopan et al [13]. The assessments of differences may be because of higher general combining ability than the specific combining ability for all the characteristics except plant height and seeds per pod brought up to be the dominance of non-additive gene effects in the outflow of these characters.…”
Section: Analysis Of Variance (Anova) For Combining Abilitysupporting
confidence: 83%
“…Thus, the significant assessments of both GCA and SCA variances indicated that both the additives and nonadditive nature of gene actions were engaged in controlling these characters in studied mungbean genotypes. These outcomes affirmed those discoveries by Reddy et al [33] Nath et al [44], Viraj et al [34], and Sopan et al [13]. The assessments of differences may be because of higher general combining ability than the specific combining ability for all the characteristics except plant height and seeds per pod brought up to be the dominance of non-additive gene effects in the outflow of these characters.…”
Section: Analysis Of Variance (Anova) For Combining Abilitysupporting
confidence: 83%
“…In this study, the application of PBRs maintained a higher chlorophyll content in leaves (Figure 3). Decreased oxidative damage (Table 1) along with the maintenance of higher auxin and cytokinin activity (Maity and Bera, 2009) might be attributed to the maintenance of chlorophyll contents (Figure 3) with the application of PBRs observed in this study. NR and MDH enzymes play an important role in plant metabolism (Scheibe, 2004).…”
Section: Discussionsupporting
confidence: 52%
“…The ANOVA for combining ability of all the characters presented in Table 2 revealed that there was highly significant differences for GCA and SCA of all the characters, indicating the preponderance of both additive and non-additive genetic components of variation involved in inheritance of all these characters of yield and component traits. The crucial importance of both additive and non-additive gene effects for inheritance of characters was also supported by Barad et al 2007, Selvam and Elangaimannan, 2010, Patil et al 2011, Nath et al 2018and Samantaray et al 2018 As apprehended from the ratio of σ 2 gca and σ 2 sca (Table 3), there was preponderance of additive gene action for the characters viz., days to 50% flowering, days to maturity and pod length and rest of the characters exhibited non-additive gene action. The characters exhibiting additive gene action were in agreement with the findings of Priya et al2012 andThamodharan et al 2017.…”
Section: Resultsmentioning
confidence: 69%